An Overview: Shyness and Career Development of Engineering Students - Masduki, Masadliahani; Zakaria, Normah; Hamzah, Norhasyimah; Rubani, Siti Nur Kamariah; Ariffin, Arihasnida (Research and Innovation in Technical and Vocational Education and Training, 2022)
Shyness is a universal problem that happens among students, including engineering students. Shy students have a high introverted trait, and they are more suitable to choose a non-social career. However, a career as an engineer requires someone to possess skills and becomes highly competent, besides not being shy to communicate and deal with various social situations. This made engineering graduates unemployed and contributed to the unemployment rate of the country. The study was conducted through Systematic Literature Review (SLR). The literature reviews in this research were obtained from Springer, IEEE, and Science direct as the core references. From 180 articles, this study only reviews 50 articles after the eligibility process. This article discusses the shyness problem and its relevance to engineering students’ career development. The strategies to eliminate shyness are also discussed in detail based on the review articles. Among the strategies that are used in previous studies were group discussion through problem-based learning, communication skills training, drama, participation in extra-curricular activities, cooperative learning, teamwork, and leadership activities.